2009
DOI: 10.1063/1.3276065
|View full text |Cite
|
Sign up to set email alerts
|

p -type conduction in beryllium-implanted hexagonal boron nitride films

Abstract: p -type conduction in hexagonal boron nitride (hBN) films was achieved by beryllium implantation and subsequent rapid thermal annealing treatment. The dependence of phase composition and electrical properties of hBN films on the implantation fluence and annealing was studied. A maximum resistivity reduction by six orders of magnitude was demonstrated. Hall measurements revealed a corresponding hole concentration of 3×1019 cm−3 and mobility of 27 cm2/V s. The activation energy of Be ions was estimated to be 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…However, no band-edge photoluminescence emissions have been observed in hBN thin films synthesized previously by various methods. 6,[12][13][14][15] As with other semiconductor materials in their development stages, realizing the band-edge photoluminescence emission at room temperature is a prerequisite in research and development towards practical applications of hBN. Metal organic chemical vapor deposition (MOCVD) is a proven technique with the ability to precisely and reproducibly deposit very thin layers (single atomic layers) to thick epilayers (tens of lm in thickness).…”
mentioning
confidence: 99%
“…However, no band-edge photoluminescence emissions have been observed in hBN thin films synthesized previously by various methods. 6,[12][13][14][15] As with other semiconductor materials in their development stages, realizing the band-edge photoluminescence emission at room temperature is a prerequisite in research and development towards practical applications of hBN. Metal organic chemical vapor deposition (MOCVD) is a proven technique with the ability to precisely and reproducibly deposit very thin layers (single atomic layers) to thick epilayers (tens of lm in thickness).…”
mentioning
confidence: 99%
“…One requirement that applies to h-BN in optical device applications is that it has high optical transmittance because the transmittance strongly determines the power conversion efficiency via the light extraction efficiency. While there have been several previous reports of sputter deposition of h-BN [9,26], the optical transmittance values of the reported layers in the DUV region were very low when compared with that of similar layers grown by MOCVD. In this paper, we report the realization of thick h-BN layers with high transmittance in the DUV region on an Al 0.7 Ga 0.3 N template that were deposited by RF magnetron sputtering under low temperature conditions.…”
Section: Introductionmentioning
confidence: 64%
“…More importantly, h-BN has a unique propensity for p-type doping. Previous reports have shown that good p-type conductivity can be achieved in h-BN via doping with Zn, Be, and Mg [9][10][11][12]. It has also been reported that the boron vacancies are acceptor-like defects with an energy level of approximately 150 meV above the valence band edge [13].…”
Section: Introductionmentioning
confidence: 99%
“…For future technological applications, physical vapor deposition methods using pulsed lasers, ion beams, or magnetron sputtering are attractive for h‐BN film growth since physical vapor deposition is adaptable to large‐scale manufacturing and modern lithography processes. Since overall device performance is dominated by the degree of film homogeneity and defects, methods need to be found that produce h‐BN thin films of controlled thickness, with large h‐BN crystalline grains uniformly distributed over large substrate areas.…”
Section: Introductionmentioning
confidence: 99%
“…While the growth of h‐BN by sputter deposition has been demonstrated several times, films are typically highly non‐uniform with a heterogeneous morphology. In this paper, we report results concerning h‐BN film crystallinity and surface morphology as probed by X‐ray diffraction (XRD) and scanning electron microscope (SEM), and it is shown that the use of a DC substrate bias during the reactive magnetron sputtering process substantially improves both the crystallinity and uniformity of the h‐BN thin films.…”
Section: Introductionmentioning
confidence: 99%